Institutional frameworks and labor market performance : comparative views on the U.S. and German economies - Buttler, Friedrich [Herausgeber]; Franz, Wolfgang [Herausgeber]; Schettkat, Ronald [Herausgeber]; Soskice, David [Herausgeber] (Routledge, 1995)
"The USA, with its tremendous job growth, is often held up as the prime example of the jobcreating power of unfettered markets, while Germany is seen as the textbook case of an overregulated European labor market stifling employment growth. For many policy advisers the lessons are clear: if Europeans want to emulate the success of Americans, they must deregulate their economies. On the other hand, economists in the USA, impressed with Germany's income growth and social stability, have shown increasing interest in the role that nonmarket institutions play in the German context. The book provides an in-depth analysis of the functioning of various labor market institutions in both the USA and Germany. In close studies of the regulatory differences between the two countries, the authors examine the impact of those insitutions on economic performance. On the basis of their findings they argue that the choise is not one between regulation and deregulation, but rather between different forms and degrees of regulation. the author discuss all the factors that influence the functioning of labor markets, including: - educational and vocational training systems -personel recruitment, selection and dismissal -work organization and hours of work -labor law and labor relations." (author's abstract, IAB-Doku) ((en)) Vergleichende Analyse der deutschen und der US-amerikanischen Arbeitsmärkte und der institutionellen Rahmenbedingungen im Hinblick auf den Grad und die Art von Regulierungen und deren Auswirkungen auf Beschäftigung und Wachstum. (IAB)
Keywords: G 2.1.1 Ökonomie / Märkte; S 4.3 Steuerung; G 1.2.1 Grund- & Strukturdaten des Arbeitsmarktes; G 2.3.1 Arbeitsteilung & -organisation; G 1.2 Arbeitsmarkt; G 1.1 Soziostrukturelle & Ökonomische Entwicklungen; G 1.2.2 Beschäftigungs- und Arbeitsverhältnisse; I 2.3.2 Nordamerika; Arbeitsmarkt; Internationaler Vergleich; Regulierung; Deregulierung; Beschäftigungsentwicklung; Arbeitszeit; Arbeitsorganisation; Arbeitsrecht; Arbeitsbeziehungen; Berufsausbildung; Arbeitsmarktpolitik; Arbeitsvermittlung; Arbeitskräftenachfrage; Personalgewinnung; Wirtschaftswachstum; Beschäftigungseffekte; Quantitative Angaben; USA